Domino 1,3-Dipolar Cycloadditions of N-Alkyl-α-Amino Esters with Paraformaldehyde: A Direct Access to α-Hydroxymethyl α-Amino Acids - Castelló, Luis M.; Nájera, Carmen; Sansano, José M. (Synthesis, 2014)
N-Alkyl-α-amino esters undergo a domino reaction, based on the iminium cation generation, with paraformaldehyde, followed by a 1,3-dipolar cycloaddition of the stabilized azomethine ylide with another equivalent of formaldehyde. The resulting products are oxazolidines, which can be transformed after hydrolysis into α-hydroxymethyl α-amino acid or its derivatives. The diastereoselective 1,3-dipolar cycloaddition was performed using sarcosine (–)-menthyl or (–)-8-phenylmenthyl esters affording the cyclic product with moderate enantiomeric ratio.
Keywords: cycloaddition; azomethine ylides; paraformaldehyde; serine